PENDUGAAN TEMPAT-TEMPAT YANG MENARIK (Point Of Interest) UNTUK MELIHAT LUTUNG ABU-ABU (Presbytis fredericae) SEBAGAI OBYEK DAYA TARIK WISATA ALAM DI TAMAN NASIONAL GUNUNG MERBABU - , Anggit Haryoso; , Dr. Satyawan Pudyatmoko, S.Hut., M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
ANGGIT HARYOSO. Prediction Places of Interest (Point of Interest) To Seeing Javan Fuscous Leaf Monkey (Presbytis fredericae) As Object Nature Tourism Attraction In Merbabu Mountain National Park. Supervised by Dr. Satyawan Pudyatmoko, S. Hut, M.Sc. Merbabu Mountain National Park designated in 2004. As a new national park, Mount Merbabu has a large untapped optimally. Included are natural tourism potential that is still continuing the previous activity that is mass tourism. Opportunities for development of nature tourism to ecotourism or sustainable nature tourism is still wide open. Special interest tourism based on wildlife Javan fuscous leaf monkey (Presbytis fredericae) can be used as an alternative tourism development in Merbabu Mountain National Park. Knowing the existence, location, and behavior of Javan fuscous leaf monkey or Rekrekan as objects of natural attractions, public perception and tourists are expected to be authorized in its development in the future. Based on visual observations using the method of Berau of Land Management on the three alternative paths (Bundas, Nggancik, Ravine Bangke), was elected as a path bangke Ravine Path wildlife tours with fixed utilizing Ascent Path existing Selo. In addition, through analysis of strengths, weaknesses, opportunities and threats, obtained four priority strategies in realizing the development of sustainable nature tourism.